(untitled) (Al-Mukhtar Journal of Legal Science, 2025)
This research examines the financial leasing contract as a complex contract involving complex financial and legal elements, combining the characteristics of leasing, ownership, and financing. This makes it an effective tool for supporting investment and enabling beneficiaries to benefit from assets without the need for immediate ownership. The study focused on the formal and substantive conditions necessary for the conclusion of this contract, such as the necessity of writing as a legal requirement and the availability of the essential elements of contracts, including consent, subject matter, and cause. The research also addressed the issue of invalidity resulting from breaching these conditions and the resulting legal consequences. The research relied on Law No. 15-2010 on financial leasing, which came to frame this type of contract in a comprehensive legal manner, clarifying its limits and conditions of validity, thus achieving balance and protecting the stability of financial transactions.